The E2F6 transcription factor is a component of the mammalian Bmi1-containing polycomb complex - Trimarchi, Jeffrey M. (The National Academy of Sciences, 2001)
The E2F transcription factors play a key role in the regulation of cellular proliferation and terminal differentiation. E2F6 is the most recently identified and the least well understood member of the E2F family. It is only distantly related to the other E2Fs and lacks the sequences responsible for both transactivation and binding to the retinoblastoma protein. Consistent with this finding, E2F6 can behave as a dominant negative inhibitor of the other E2F family members. In this study, we continue to investigate the possible role(s) of E2F6 in vivo. We report the isolation of RYBP, a recently identified member of the mammalian polycomb complex, as an E2F6-interacting protein. Mapping studies indicate that RYBP binds within the known “repression domain” of E2F6. Moreover, we demonstrate that endogenous E2F6 and polycomb group proteins, including RYBP, Ring1, MEL-18, mph1, and the oncoprotein Bmi1, associate with one another. These findings suggest that the biological properties of E2F6 are mediated through its ability to recruit the polycomb transcriptional repressor complex.